2359. Evaluating Hepatitis C Virus (HCV) Diagnostic Testing, Cure and Reinfection among People Living with HCV and HIV Coinfection in New York City. (15th December 2022) - Graf, Laura; Bocour, Angelica; Huang, Yanting Kelly; Romano, Anthony; Varigonda, Renuka; McPherson, Tristan D
Abstract: Background: Untreated hepatitis C virus (HCV) infection can lead to liver disease, cancer and premature death; HIV coinfection can accelerate adverse outcomes. People living with HIV (PLWH) should be screened for HCV with an antibody test at least once and more frequently if other risk factors. A diagnostic HCV RNA test should be used to determine cure/clearance (RNA-negative) vs active infection (RNA-positive). Among people with HCV/HIV coinfection in New York City (NYC), we aimed to 1) describe HCV testing, cure/clearance, reinfection and identify disparities; 2) assess relative timing of HCV/HIV coinfection diagnosis to evaluate HCV testing among PLWH. Methods: PLWH as of September 30, 2021 were matched to people with a positive HCV test July 1, 2014–December 31, 2020; HCV test results through December 31, 2021 were used for analyses and to observe cure. A HCV clearance cascade was created to evaluate testing, cure/clearance and reinfection, and was stratified by age, sex and race/ethnicity. Timing of coinfection was assessed for people with new HCV/HIV diagnoses January 1, 2014–December 31, 2020 to identify recent trends. Coinfection date was defined as the later HCV or HIV diagnosis date. Results: There were 11, 137 PLWH with any positive HCV test. Of these, 10, 773 (97%) had an RNA test; 8, 926 (83%) had initial active infection; 6, 901 (77%) had cure/clearance and 302 (4%) with cure/clearance were reinfected (Figure 1). Black Non-Hispanic (NH) people and those aged 20–39 had a high burden of active infection, with 3, 653 (87%) and 803 (93%), respectively. Both groups had proportionally lower cure/clearance (77% and 63%, respectively) compared to Asian NH people (86%) and people ≥ 60 (81%) having the highest proportions. Most people with recent coinfections were diagnosed with HIV prior to HCV (annual range: 39%–71%) (Figure 2). Conclusion: HCV diagnostic testing and cure/clearance were high and reinfection was low among people with coinfection in NYC. Most people with coinfection had HCV RNA tests, indicating appropriate HCV testing in this population. Cure/clearance could be improved among younger and Black NH people; provider and patient education might improve outcomes. To initiate timely treatment, providers should continue screening PLWH for HCV as HIV infection often precedes HCV infection. Disclosures: All Authors : No reported disclosures.